A facile forward-genetic screen for Arabidopsis autophagy mutants reveals twenty-one loss-of-function mutations disrupting six ATG genes. Issue 6 (3rd June 2019) - Young, Pierce G.; Passalacqua, Michael J.; Chappell, Kevin; Llinas, Roxanna J.; Bartel, Bonnie
ABSTRACT: Macroautophagy is a process through which eukaryotic cells degrade large substrates including organelles, protein aggregates, and invading pathogens. Over 40 autophagy-related ( ATG ) genes have been identified through forward-genetic screens in yeast. Although homology-based analyses have identified conserved ATG genes in plants, only a few atg mutants have emerged from forward-genetic screens in Arabidopsis thaliana . We developed a screen that consistently recovers Arabidopsis atg mutations by exploiting mutants with defective LON2/At5g47040, a protease implicated in peroxisomal quality control. Arabidopsis lon2 mutants exhibit reduced responsiveness to the peroxisomally-metabolized auxin precursor indole-3-butyric acid (IBA), heightened degradation of several peroxisomal matrix proteins, and impaired processing of proteins harboring N-terminal peroxisomal targeting signals; these defects are ameliorated by preventing autophagy. We optimized a lon2 suppressor screen to expedite recovery of additional atg mutants. After screening mutagenized lon2-2 seedlings for restored IBA responsiveness, we evaluated stabilization and processing of peroxisomal proteins, levels of several ATG proteins, and levels of the selective autophagy receptor NBR1/At4g24690, which accumulates when autophagy is impaired. We recovered 21 alleles disrupting 6 ATG genes: ATG2/At3g19190, ATG3/At5g61500, ATG5/At5g17290, ATG7/At5g45900, ATG16/At5g50230, and ATG18a/At3g62770 . Twenty alleles were novel, and 3 of the mutated genes lack T-DNA insertional alleles in publicly available repositories. We also demonstrate that an insertional atg11 / At4g30790 allele incompletely suppresses lon2 defects. Finally, we show that NBR1 is not necessary for autophagy of lon2 peroxisomes and that NBR1 overexpression is not sufficient to trigger autophagy of seedling peroxisomes, indicating that Arabidopsis can use an NBR1-independent mechanism to target peroxisomes for autophagic degradation. Abbreviations: ATG: autophagy-related; ATI: ATG8-interacting protein; Col-0: Columbia-0; DSK2: dominant suppressor of KAR2; EMS: ethyl methanesulfonate; GFP: green fluorescent protein; IAA: indole-3-acetic acid; IBA: indole-3-butyric acid; ICL: isocitrate lyase; MLS: malate synthase; NBR1: Next to BRCA1 gene 1; PEX: peroxin; PMDH: peroxisomal malate dehydrogenase; PTS: peroxisomal targeting signal; thiolase: 3-ketoacyl-CoA thiolase; UBA: ubiquitin-associated; WT: wild type